OPTIMASI KEKASARAN TERHADAP PERMUKAAN MATERIAL VCN 150 PADA PROSES BUBUT CNC DENGAN METODE RESPON SURFACE - Trisna Fitri Mutiari; Zaldy Kurniawan; Eko Yudo (Politeknik Manufaktur Negeri Bangka Belitung, 2022)
Turning is a metal cutting process that changes the geometry of a material. In this turning process there is a response to be obtained, namely the lowest shaft surface roughness value. Therefore, it is necessary to set the right process variables in order to produce the best roughness value. In this study using the Response Surface Methodology, namely Box-Behnken Design. The purpose of this study was to determine the right combination of levels from the combination of variables in the CNC lathe machining process on VCN 150 material so as to optimize the roughness value. Variables that are thought to have an effect on the surface roughness of VCN 150 material are cutting speed with levels (120 m/minute, 140 m/minute and 160 m/minute), feeding speed with levels (0.14 mm/turn, 0.21 mm/minute). revolutions and 0.28 mm/rev) and depthof cut with levels (0.5 mm, 0.75 mm and 1 mm). The surface roughness value with the lowest value with each variable is the cutting speed of 120 m/min (level 1), the depth of cut is 0.75 mm (level 2), and the feeding speed is 0.28 mm/minute (level 3) the roughness value is 0.468 m.